Identification of a sequence within U5 required for human immunodeficiency virus type 1 to stably maintain a primer binding site complementary to tRNA(Met). - Kang, S M (1997)
Initiation of reverse transcription of human immunodeficiency virus type 1 (HIV-1) occurs by extension from the 3' end of a cellular tRNA complexed to the primer binding site (PBS) located near the 5' end of the viral RNA genome. Although the PBSs for all naturally occurring HIV-1 viruses are complementary to the 3'-terminal 18 nucleotides of tRNA(Lys)3, we identified an HIV-1 virus which contained a PBS complementary to the 3' nucleotides of tRNA(Met); the PBS of this virus was not stable upon extended culture and reverted back to the wild type (S.-M. Kang, J. K. Wakefield, and C. D. Morrow, Virology 222:401-414, 1996). To further characterize the virus with a PBS complementary to tRNA(Met), a DNA fragment encompassing the PBS and U5 region from this proviral genome was substituted for the same region in the infectious HIV-1 proviral clone [named pHXB2(AC-Met)]. Three additional proviral genomes were also created: pHXB2(Met), which is isogenic with pHXB2 except for the PBS complementary to tRNA(Met); pHXB2(Met-AC-Met), which contains the PBS sequence complementary to the 3'-terminal nucleotides and the sequence upstream of this PBS in U5 complementary to the anticodon region of tRNA(Met); and pHXB2(Met-C-Met), which contains two G-to-C changes predicted to disrupt complementarity within the tRNA(Met) anticodon region. Viruses derived from the transfection of these proviral genomes were infectious, although the appearance of the viruses was delayed compared to that of the wild-type virus. PCR amplification and DNA sequence analysis of the PBS regions from proviral genomes revealed that the PBSs from viruses derived from pHXB2(Met) and pHXB2(AC-Met) reverted back to the wild type by days 16 and 44 postcoculture, respectively. Two new, novel mutant viruses were identified among viruses derived from pHXB2(Met-C-Met) at day 35 postcoculture: one contained a PBS complementary to tRNA(Lys)1,2, while the second maintained a PBS complementary to tRNA(Met) but contained a 26-nucleotide deletion in U5 upstream of the anticodon-complementary region. By day 125 postcoculture, the PBS in the virus from this culture had reverted back to the wild type, complementary to tRNA(Lys)3. In contrast, the viruses derived from pHXB2(Met-AC-Met) stably maintained a PBS complementary to tRNA(Met) during the 125-day culture period examined. The results of these studies support the idea that HIV-1 can maintain a PBS complementary to alternative tRNAs provided that the appropriate complementarity exists between the U5-PBS region of the viral RNA genome and the tRNA molecule used to initiate reverse transcription.